POLYPHENOLIC COMPOSITION AND ANTIOXIDANT CAPACITY IN THE BRANCHES AND LEAVES OF SELECTED PRUNUS AND PYRUS SPECIES - Jurić, Tatjana; Ždero Pavlović, Ružica; Petković, Milica; Radević, Jelena; Hourani, Sara; Popović, Boris M. (Food and Feed Research, 2025)
Plants of the genus Prunus and Pyrus have been valued and used for centuries due to their rich nutritional and therapeutic properties. The fruit itself is primarily consumed, while other parts of the plants are often overlooked despite their biological activity. In this study, branches and leaves of 10 plant species were investigated, including nine from the Prunus genus (wild P. avium, cultivated P. avium, P. mahaleb, P. fruticosa, P. cerasus, P. domestica, P. persica, P. cerasifera, P. cerasifera pissardii) and one from the Pyrus genus (P. communis). This study aimed to determine their polyphenolic composition and antioxidant capacity. The powders from branches and leaves of Prunus and Pyrus species were extracted in 70% ethanol using ultrasound. The quantitative analysis of polyphenols involved spectrophotometric determination of total phenolic content, total flavonoid content, total hydroxycinnamic acid content, and total anthocyanins content. The study evaluated the antioxidant capacity of branches and leaves using FRAP and DPPH assays. Pyrus communis demonstrated the highest total phenolic content in both branches (591.55 mg gallic acid equivalents/g dry weight) and leaves (685.62 mg GAE/g d. w.). P. communis also showed strong antioxidant potential in both assays. Among Prunus species, P. cerasifera pissardii demonstrates an exceptional antioxidant capacity, and a high amount of total anthocyanins, phenolic acids, and total phenols. This study provides a preliminary insight into the phytochemical profile of underutilized by-products, such as branches and leaves. These parts of plants can also generally be regarded as valuable resources of biologically significant compounds. Based on the results, we can conclude that by-products from Pyrus communis and Prunus cerasifera pissardii have the potential for wider chemical and biological investigations.
Keywords: plum; pear; by-products; antioxidant activity; polyphenols